KAJIAN SEMIOTIKA ROLAND BARTHES PADA FEED INSTRAGAM TRI PASCA MERGER DENGAN INDOSAT - Bobby Halim; Mukhsin Patriansah (Narada : Jurnal Desain dan Seni, 2023)
The author is interested in researching the Tri account's Instagram feed after the merger with Indosat because each operator has a social media account, especially Instagram. After the two operators merged, of course the two operators thought about and displayed advertisements and information with a new concept. The research method used is Roland Barthes' semiotic analysis because it is a tool to explore the sign system behind the visual content of Tri's Instagram account. This research is also qualitative in nature so that it can produce research that is thorough, argumentative and can be a reference for further research. The results obtained based on this research are Tri Caring for Young People's Achievements, Educating on the Importance of Investment, Supporting the Progress of Indonesian Women and Supporting Content Creators.